2007
DOI: 10.1097/nen.0b013e3181256b4c
|View full text |Cite
|
Sign up to set email alerts
|

Desmin Is Oxidized and Nitrated in Affected Muscles in Myotilinopathies and Desminopathies

Abstract: Degenerative diseases with abnormal protein aggregates are characterized by the accumulation of proteins with variable posttranslational modifications including phosphorylation, glycoxidation, oxidation, and nitration. Myofibrillar myopathies, including myotilinopathies and desminopathies, are characterized by the intracytoplasmic focal accumulation of proteins in insoluble aggregates in muscle cells. By using single immunohistochemistry, monodimensional gel electrophoresis and Western blotting, and bidimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 49 publications
3
35
0
4
Order By: Relevance
“…The reason why desmin is a preferential target of AGE in the cardiomyocytes remains elusive for now. Partial colocalization of AGE adducts and desmin aggregates was reported in skeletal muscle fibers from patients suffering from desminopathies, suggesting that desmin is prone to AGE adduct modifications in the context of muscle disease (36). Interestingly, vimentin, another type III intermediate filament protein closely related to desmin, is also a preferential target of AGE in the senescent fibroblast where it participates in aggresome formation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The reason why desmin is a preferential target of AGE in the cardiomyocytes remains elusive for now. Partial colocalization of AGE adducts and desmin aggregates was reported in skeletal muscle fibers from patients suffering from desminopathies, suggesting that desmin is prone to AGE adduct modifications in the context of muscle disease (36). Interestingly, vimentin, another type III intermediate filament protein closely related to desmin, is also a preferential target of AGE in the senescent fibroblast where it participates in aggresome formation (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Diguet et al (2011) demonstrated that, in dilated cardiomyopathy, oxidatively damaged desmin progressively loses its striated pattern and accumulates in the sarcoplasm. Desmin has been found to be particularly susceptible to the formation of AGEs and to damage by lipid peroxidation end-products in animal models of tissue ischemia and reperfusion (Canton et al 2004;Janue et al 2007a;Janue et al 2007b). AGEs and lipid peroxidation end-products accumulate in PAD muscle and, particularly, in PAD myofibers (Norgren et al 2007;Pipinos et al 2008Pipinos et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of myofibrillar myopathies have shown that ROS and reactive nitrogen species (RNS) damage cytoskeletal and other proteins and impair their processing through the ubiquitin-proteasome pathway, favoring accumulation of non-degraded damaged proteins as protein aggregates (Clemen et al 2013;Janue et al 2007a;Janue et al 2007b). Desmin is a key target for oxidative and nitrosative damage in myofibrillar myopathies (Janue et al 2007a;Janue et al 2007b), leading to inactivation and misfolding of the protein and exposing hydrophobic surfaces for protein-protein interactions, which promote aggregation (Grune et al 1997;Janue et al 2007a;Janue et al 2007b). Furthermore, desmin is a preferred site for the development of advanced glycation end products (AGEs) in cardiomyopathies, both in mice and in humans (Diguet et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Modified desmin can be considered to be an additional element in the pathogenesis of MFM. In addition to desmin, pyruvate kinase muscle splice form M1 is oxidised in muscule tissues, thus supporting complemental mitochondrital damage, at least in some cases of myotilinopathy [40]. Together, these observations support a link between oxidative stress, protein aggregation and abnormal protein deposition in MFMs.…”
Section: Protein Degradationmentioning
confidence: 67%